2015
DOI: 10.1186/s12974-015-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Humoral factors in ALS patients during disease progression

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a neurodegenerative disease affecting upper and lower motor neurons in the CNS and leading to paralysis and death. There are currently no effective treatments for ALS due to the complexity and heterogeneity of factors involved in motor neuron degeneration. A complex of interrelated effectors have been identified in ALS, yet systemic factors indicating and/or reflecting pathological disease developments are uncertain. The purpose of the study was to identify humo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 105 publications
7
88
0
Order By: Relevance
“…Similar to the results in CSF, increases in levels of inflammatory factors (IL-6 and IL-8) were also observed [134]. However, in contrast to levels in the CSF, decreases in immune factors (IL-5 and IL-2) and glutathione levels were also shown indicating decreased immune response with increased oxidative stress.…”
Section: Biomarkers Of Inflammationsupporting
confidence: 80%
“…Similar to the results in CSF, increases in levels of inflammatory factors (IL-6 and IL-8) were also observed [134]. However, in contrast to levels in the CSF, decreases in immune factors (IL-5 and IL-2) and glutathione levels were also shown indicating decreased immune response with increased oxidative stress.…”
Section: Biomarkers Of Inflammationsupporting
confidence: 80%
“…The authors suggested that the elevation in IL-8 was mediated by activated microglia leading to a pro-inflammatory cascade in ALS brain. Levels of cytokines and chemokines have been measured in peripheral blood samples taken from ALS patients and controls [24]. A number of inflammatory mediators including IL-8 exhibited significant increases in blood from ALS individuals.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Some studies were limited by the number of samples in the analysis (Turner et al., 2013), and some chose a different control population into the study (Tateishi et al., 2010). In addition, a panel of biomarkers has been detected in either the CSF or serum in some recent studies, but they were either more concerned with a diagnosis rather than a clinically relevant prognosis (Gray et al., 2015; Kuhle et al., 2009; Lawton et al., 2012) or only measuring factors either the CSF or serum (Ehrhart et al., 2015; Mitchell et al., 2009). …”
Section: Introductionmentioning
confidence: 99%